Relationship of Knowledge and Attitude with Mother's Actions on Stunting Incidents in Wali Ate Village - Karolus Wulla Rato (Institute of Computer Science (IOCS), 2022)
Stunting is a child's growth and development disorder caused by lack of nutrition, infection, or inadequate stimulation. This study aims to examine the relationship between mother's knowledge and attitudes and mother's actions with the incidence of stunting in Wali Ate Village. research was carried out on20 june to 3 july 2022.Objective: To determine the relationship between knowledge and attitudes with mother's actions on the incidence of stunting in Wali Ate Village. Methods: Analytical research with a cross sectional approach. The population in this study amounted to 887 mothers. The number of samples was 96 mothers. The sampling technique used Accidental Sampling. Data collection by using a questionnaire. Results: Most of the respondents have sufficient knowledge aboutstunting42 people (43.8%). A number of respondents have a supportive attitude towards preventionstunting70 people (72.2%). Mother's actions on preventionstuntingwere in moderate action as many as 48 people (50.0%). The test results obtained a probability value for the relationship of knowledge with the mother's actions in the eventstuntingof 0.617 (p>0.05), while the relationship between attitudes and maternal actions in preventing DHF was 0.66 (p>0.05).